Literasi Digital Society Menuju Era Perubahan Pertumbuhan Ekonomi Di Kelurahan Tanah Mas Banyuasin Sumatera Selatan - Marleni; Trecy Austin; Diany Putri Pratiwi; Indah Pusnita (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Digital literacy includes a deep understanding of technology, the ability to access, evaluate and effectively use information presented in digital media, as well as active participation in an increasingly complex digital world. In the context of the digital economy, business actors do not only compete with local competitors, but also with global competitors that can be accessed through digital platforms. Wider connectivity has opened up access to international markets, enabling cross-border transactions without significant geographic barriers. Tanah Mas Banyuasin Village in South Sumatra has unique characteristics in the context of digital literacy and economic growth. Tanah Mas has diverse economic potential, ranging from the commercial sector, fertile agriculture to various traditional crafts. However, like in many other regions in Indonesia, economic, infrastructure and digital literacy challenges remain. The existence of digital literacy makes it easier for people to communicate through existing social media and will have an impact on the development of insights in society to improve economic life in the future.